Natural excipients with multifunctional uses and their preparation process

Through the twin-screw hot melt extrusion process, coconut shells and polyvinyl compounds are combined to develop high-functional, biodegradable multifunctional auxiliary agents, which solves the problem of insufficient water absorption and liquid absorption performance of pharmaceutical dosage forms in the prior art, and improves lubrication and retention effects.

JP7657496B2Active Publication Date: 2025-04-07REGERON INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023558618
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-02
Filing Date
2022-12-02
Publication Date
2025-04-07
Estimated Expiration
2042-12-02

AI Technical Summary

Technical Problem

The prior art is difficult to develop highly functional, sustainable natural absorbers and lubricants for improving water absorption and other liquid absorption properties of pharmaceutical dosage forms while avoiding the use of harmful synthetic silicon-based auxiliary agents.

Method used

Through the twin-screw hot melt extrusion process, coconut shells and/or coconut fiber powders are used as natural materials and processed with polyvinyl compounds (such as glycerol, glucosol, polyvinyl alcohol, propyl alcohol, etc.) to prepare a multifunctional auxiliary agent with high functional and biodegradable properties.

Benefits of technology

It achieves efficient water absorption and liquid retention performance, and has lubricating effects, extends the shelf life and transportation stability of the drug, and provides multifunctional improvements to drug dosage forms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657496000008
    Figure 0007657496000008
  • Figure 0007657496000009
    Figure 0007657496000009
  • Figure 0007657496000010
    Figure 0007657496000010
Patent Text Reader

Abstract

A multifunctional natural absorbent excipient developed by twin-screw hot melt extrusion process is disclosed.The present invention discloses a natural excipient composition comprising: (a) natural coconut husk, and / or coconut husk, coir apis powder derived from the fruit of Cocos nucifera; and (b) at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG) and combinations thereof, wherein the weight ratio of (a) to (b) ranges from 1:1 to 6:4.
Need to check novelty before this filing date? Find Prior Art

Description

Detailed Description of the Invention

[0001] [Technical field] The present invention relates to the continuous production of water-absorbing excipients using a twin-screw hot melt extrusion process. The present invention is also directed to the continuous production of biodegradable natural water-absorbing agents with multifunctional applications. The prepared functional excipients can be used in pharmaceuticals, nutraceuticals and cosmetics. More specifically, the present invention relates to novel co-processed excipients obtained from coconut husk, the fruit of Cocos nucifera, that improve water absorption and / or other liquid absorption properties of different dosage forms.

[0002] [Background technology] Therapeutic and non-therapeutic drug products consist of two parts: the active ingredient (drug / active ingredient) and the inactive ingredients (excipients) that serve to bind the formulation, extend its mass, mask its bitterness, etc. Binders, gums, sugars, etc. are common "excipients" that have no therapeutic activity but are needed to be added to the dosage form, e.g. tablets, capsules, ointments, creams, or syrups.

[0003] Excipients play a vital role in the development process of various dosage types and their administration. Inappropriate selection of excipients can also cause extreme intoxication, as evidenced by epilepsy patients taking phenytoin capsules in Australia in the late 1960s (Furrer, P., 2013). Calcium sulfate, which was used as a diluent in capsules, was replaced by lactose, which was perceived as harmless and thus allowed phenytoin to be delivered safely. Most formulations contain higher concentrations of excipients than the active ingredient, and as a result, excipients have a crucial impact on the processability, stability, safety, and performance of different formulations. The majority of currently available excipients do not meet the desired set of functionalities, and therefore there is an urgent need to develop high-functionality excipients. Broad-functionality excipients can be obtained by inventing novel chemical excipients, better grades of approved excipients, and new configurations of existing excipients. (Kaushik et al.)

[0004] The chart below (Figure 1) shows the high-functionality excipients present on the market. As shown in the figure, some high-functionality excipients, for example Ludipress, can be used not only as a diluent but also as a lubricant, thus simultaneously imparting two or more functionalities in the formulation. Other co-processed excipients may also be widely applicable. Colloidal silicon dioxide has been used as an absorbent for nearly 70 years. The first scientific literature on the use of AEROSIL® fumed silica as a pharmaceutical excipient was published in 1957. Since then, "AEROSIL® 200 Pharma" has become accepted and recognized as a pharmaceutical excipient. Although the US Food and Drug Administration (FDA) had already recognized silicon dioxide as a safe food additive, people have witnessed serious side effects from silicon dioxide when it was used in various formulations as an absorbent. In 2018, the European Food Safety Authority recommended the implementation of stricter guidelines on the use of silicon dioxide to the European Union before more research was conducted (EFSA Journal).

[0005] Coconut husk and / or coir pith flour are among the natural lignocellulosic fibers commonly used in many applications today. The fruit of the tropical palm plant, coconut, Cocos nucifera, is widely cultivated in coastal regions of tropical countries. In Malaysia, coconut appears to be the fourth most traditionally produced crop after palm oil, rubber, and paddy rice. Coconut husk is present in significant quantities in many regions as a residue from coconut processing, resulting in a variety of coarse core fibers, which are seed hair fibers derived from the coconut outer shell. The abundance of coconut husk and / or coir pith flour makes it possible to find potentially valuable lignocellulosic feedstocks for conversion into pulp and paper from a raw material source (Main et al., 2014).

[0006] Although coconut husk and / or coir pith powder has many potential benefits, this raw material is underutilized for productive purposes despite its large quantities. Significant quantities of coconut husk and / or coir pith powder accumulate annually near coir processing plants, causing serious disposal problems and fire risks. Due to its high content of lignin and cellulose (about 40%) and high content of polyphenols (about 100mg / 100g coir pith), its decomposition and mineralization rate is very slow under natural conditions, resulting in long stability of the compounds. India has a production capacity of about 280,000 tonnes of coconut husk and / or coir pith powder. This could make this valuable organic resource a significant source for domestic utilization and export. Lignin prevents easy decomposition and mineralization of coconut husk and / or coir pith powder. Lignin is a three-dimensional amorphous aromatic heteropolymer containing stable C-C and ether-ester bonds between monomeric single- or double-methoxylated phenylpropylphenol units and is a recalcitrant biopolymer. Lignin degradation is often dependent on the availability of metabolically accessible co-substrates such as glucose (Prabhu et al., 2002).

[0007] Lignin is a type of complex organic polymer that forms the main structural material and is particularly important in cell walls, especially in wood and bark, because it provides rigidity and does not decay easily. Chemically speaking, lignin is a cross-linked phenolic polymer. Lignin is the second most abundant biopolymer in lignocellulosic biomass after cellulose. Lignin is tightly bound by non-covalent or covalent bonds to form carbohydrate complexes with cellulose and hemicellulose. Lignin has diverse pharmacological activities, such as antitumor, antihyperglycemic, antibacterial, anti-HIV, and antioxidant activities, but in contrast to polysaccharide-based materials, lignin has not yet been widely exploited in the biomedical field (Spiridon et al., 2018).

[0008] The name Cocos nucifera comes from the Portuguese word coco, meaning "head" or "skull," and nucifera, which comes from the Latin words nux (fruit) and fera (to bear fruit). Cocos nucifera is a plant that belongs to the palm family. There are two types of coir fiber, namely brown fiber and white fiber. Brown fiber comes from fully ripe coconuts, which have properties such as thickness, durability, and high abrasion resistance, and is most commonly used in civil engineering works. On the other hand, white fiber comes from unripe coconuts, which, in addition to having lower strength, are smoother and finer. It has been pointed out that by incorporating the fiber into concrete, the high lignin and low cellulose nature of coconut coir may not only slightly increase the concrete strength and give it its solidity, but also create a special interfacial transition zone in the concrete that may affect the compressive strength. It has been shown that improved tensile strength can be achieved by adding coir fibres at the optimum concrete formation stage ( Dhanasree et al., 2019 ).

[0009] Coconut husk and / or coir pith powder is a spongy, fluffy, light material with improved water retention and high compressibility. The pH of regular pith is acidic, while composted coir pith is closer to neutral (Ghosh et al., 2007).

[0010] Co-processing here refers to the use of waste as a renewable raw material or energy source, or both (material recycling), with or without other raw materials. Co-processing is the integration of two or more raw materials (including waste) to form a material with superior functionality in an optimal component ratio, resulting in minimal unwanted residues. Co-processing is essentially based on particle engineering, allowing primary excipients to change their Critical Material Properties (CMAs). Such improvements should be reflected in improved characteristics of the resulting co-processed content.

[0011] DISCLOSURE OF THEINVENTION [Technical issues] The present invention discloses one such novel excipient obtained from the processing of natural sources that is not an "active ingredient" per se, but when added to a formulation, can improve the efficacy of the formulation in various aspects.

[0012] It has been recognized that the industrially scalable continuous production of novel excipients obtained from co-processing of natural sources and combinations thereof has not been previously disclosed.

[0013] The main objective was to develop novel biodegradable natural excipients acting as absorbents as well as lubricants in the design of various pharmaceutical, nutraceutical and / or cosmetic formulations, which could be a good alternative to synthetic silicone-based excipients.

[0014] Another objective of the presented business relates to developing biodegradable natural excipients by twin-screw hot melt extrusion technology as a one-step, non-aqueous, industrially scalable and continuous manufacturing process, thereby avoiding the need to evaporate large amounts of water in wet conditions such as wet granulation, especially in humidity and heat sensitive formulations, thus saving production time and costs.

[0015] Another object of the present invention is to provide an excipient that has good water absorption and lubricity, thereby retaining moisture and preventing drying, resulting in easier handling, packaging, distribution, and longer shelf life.The biodegradable natural water absorbent of the present invention (i.e., coconut husk and / or coconut husk derived coir piss powder) has a water absorption capacity of at least 8-10 times its own weight within 3 hours of exposure to water.

[0016] It is a further object of the present invention to provide a natural excipient with multiple applications such as thickener, softener, rheology control agent and storage stability enhancer in semi-solid and liquid dosage forms, as well as a source of dietary fiber in the design of various pharmaceutical, nutraceutical and / or cosmetic formulations.

[0017] Another object of the present invention is to disclose that the novel excipient is biodegradable natural coconut husk and / or coconut husk, coir piss powder from the fruit of Cocos nucifera, co-processed with at least one polyol compound. This co-processed excipient obtained from a biodegradable natural source, i.e. coconut husk (fruit of Cocos nucifera), by co-processing with at least one polyol compound, can replace synthetic (and / or natural) absorbents or lubricants used in the production of different solid, semi-solid, and / or liquid formulations, and the same excipient material (i.e. coconut husk and / or coir piss powder) can function as both absorbent and lubricant in the formulation. Therefore, this material is ideal for the preparation of different solid, semi-solid, and / or liquid formulations that require both water and / or other fluid absorption and lubrication at the same time.

[0018] Another object of the present invention is to develop a biocompatible transdermal patch comprising high content of the proposed natural excipients to retain and release the active substances in a controlled manner to elicit desired therapeutic, nutraceutical and cosmetic effects, particularly to deliver drugs locally to relieve pain caused by Rheumatoid Arthritis (RA) by use of known anti-inflammatory oils and other Active Pharmaceutical Ingredients (APIs).

[0019] Another object of the present invention is to develop a natural excipient based solid self-emulsifying drug delivery system (SMEDDS) powder for efficient treatment of topical antifungal infections, which may have high content and solubility of active substance.

[0020] Another objective of the present invention is to develop a novel biocompatible self-adhesive hydrogel film platform using natural excipients that can overcome the process limitations of current formulations for wound healing and cosmetic skin rejuvenation / anti-aging properties.

[0021] [Means for solving the problems] Disclosed herein are biodegradable natural absorbent excipients with multiple functionalities developed by a twin-screw hot melt extrusion process.

[0022] In one aspect of the present disclosure, there is provided a natural excipient composition comprising: (a) natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera; and (b) at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof, wherein the weight ratio of (a) to (b) is in the range of 1:1 to 6:4.

[0023] In one embodiment of the present disclosure, there is provided a process for preparing a natural excipient composition (FIG. 2) comprising: (a) natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera; and (b) at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof, wherein the weight ratio of (a) to (b) ranges from 1:1 to 6:4, said process comprising the steps of: (c) milling the coir pith and / or powder thereof derived from coconut husk using a rotary cutter mill having a standard sieve; nucifera fruits by cutting and size reduction process; and (d) mixing coconut husk and / or coir pith powder with at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof in a gravimetric hopper; e) processing the mixture at high temperature by twin screw hot melt extrusion, where the process parameters and the ratios of the mixture can be optimized to obtain a uniform product with desired attributes.

[0024] BRIEF DESCRIPTION OF THE DRAWINGS [Figure 1] Shows some highly functional excipients available on the market. [Figure 2] Experimental design for preparing co-processed multifunctional novel excipients. FIG. 3 shows the FTIR analysis of the functional excipients described in this invention. [Figure 4] SEM of co-processed multifunctional novel excipient. [Figure 5] Particle size distribution of co-processed multifunctional new excipients. Figure 6: In vitro drug release study with HPTLC batch densitogram of formulation batch F6. [Figure 7] Paw edema measurements: a) 0 min, b) 60 min, c) 120 min, d) 180 min, e) 240 min. (Note: Data are expressed as mean ± SEM and analyzed by one-way ANOVA followed by Bonferroni's multiple comparison post-test). [Figure 8] IL-6 measurements from transdermal patches (Note: data are expressed as mean ± SEM and analyzed by one-way ANOVA followed by Bonferroni's multiple comparison post-test). [Figure 9] PXRD patterns of the formulation and raw material. [Figure 10] Antifungal activity using the petri dish plate method. [Figure 11] Skin irritation test results: A) initial; B) 24 hours; C) 48 hours; D) 72 hours.

[0025] BEST MODE FOR CARRYING OUT THEINVENTION <Definition> For convenience, before further description of the present disclosure, certain terms and examples used herein are collected here.These definitions should be read in light of the remaining parts of the present disclosure and should be understood by those skilled in the art.Terms used herein have meanings that are recognized and known to those skilled in the art, but for convenience and completeness, certain terms and their meanings are provided below. The articles "a", "an" and "the" are used to refer to one or to more than one (i.e. to at least one) of the grammatical object of the article.

[0026] The terms "comprise" and "comprising" are used in an inclusive and open sense, meaning that additional elements may be included. They are not intended to be interpreted as "consisting only of."

[0027] Throughout this specification, unless the context otherwise requires, the word "comprise", and variations such as "comprises" and "comprising", are understood to imply the inclusion of stated elements or steps, or groups of elements or steps, but not the exclusion of other elements or steps, or groups of elements or steps.

[0028] The term "including" is used to mean "including but not limited to." "Including" and "including but not limited to" are used interchangeably.

[0029] The term "at least one" is used to mean one or more and therefore includes mixtures / combinations as well as individual components.

[0030] Ratios, concentrations, amounts, and other numerical data may be presented herein in a range format, with it being understood that such range formats are used merely for convenience and brevity and should be interpreted flexibly to include not only the numerical values ​​expressly recited as the limits of the range, but also all of the individual numerical values ​​or subranges subsumed within the range, as if each numerical value and subrange were expressly recited.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this disclosure belongs.Although any method and material similar or equivalent to those described herein can be used in the practice or testing of this disclosure, preferred methods and materials are described here.All publications mentioned herein are incorporated herein by reference.

[0032] "Hot melt extrusion" (HME) is a process in which co-processed excipients are prepared by applying heat and pressure to force the product through an orifice in a continuous process. HME is carried out using an extruder, a barrel containing one (single screw) or two co- / counter-rotating screws (twin screw), which transport the material down the barrel.

[0033] The terms "co-processing" or "co-processed" refer to the use of waste materials as a renewable feedstock, energy source, or both (materials recycling), with or without other materials. Co-processing is the integration of two or more raw materials (including waste materials) that can be combined in optimal component ratios to form a material with superior performance, resulting in minimal unwanted residual materials.

[0034] The present disclosure is not to be limited in scope by the specific embodiments described herein, which are for the purpose of illustration only. Functionally equivalent products, compositions, and methods are clearly within the scope of the present disclosure, as described herein.

[0035] Hot melt extrusion (HME) is a new solvent-free polymer processing approach currently being explored by both industry and academia as a means to provide a variety of dosage forms with improved end product compatibility. Additionally, HME offers the ability to make finished products cycle faster and more productive by reducing production steps.

[0036] Functional excipients have been formulated to modify / take advantage of their basic properties through hot melt extrusion processes (Crowley et al., 2007, Li et al., 2015). In one embodiment of the present disclosure, multifunctional novel excipients were prepared using natural coconut husk and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera and at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof, using twin screw hot melt extrusion.

[0037] In one embodiment of the present disclosure, natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof were used to prepare a multifunctional novel excipient using twin-screw hot melt extrusion, wherein the temperature range of the twin-screw hot melt extrusion was 60-110°C, and the screw speed was in the range of 25-60 rpm.

[0038] The details of the optimization ratios are shown in Table 1 below:

[0039] [Table 1]

[0040] In one embodiment of the present disclosure, based on the observations in Table 1, natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof were selected in the ratio range of 1:1 to 6:4, respectively, to prepare a multifunctional novel excipient using twin-screw hot melt extrusion.

[0041] More specifically, in one embodiment of the present disclosure, at least one polyol compound consisting of natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and glycerol and combinations thereof were used in the range of 1:1 to 6:4 as the final optimized allocation for further characterization and formulation.

[0042] In one embodiment of the present disclosure, the simple polyol compound is glycerol (also called glycerin or glycerine). It is a colorless, odorless, viscous liquid that is non-toxic and sweet-tasting. The glycerol backbone is found in lipids called glycerides. It is widely used in FDA-approved wound and burn treatments due to its antibacterial and antiviral properties. It is also used as a useful marker to measure liver disease. It is still commonly used in the food industry as a sweetener and in prescription formulations as a humectant. Glycerol is miscible with water and hygroscopic due to its three hydroxyl groups (en.wikipedia.org).

[0043] In one embodiment of the present disclosure, natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof, were selected in an allocation range of 1:1 to 6:4, respectively, to prepare a multifunctional novel excipient using twin-screw hot melt extrusion, wherein the Carr index of said allocation was in the range of 28 to 13%.

[0044] In one embodiment of the present disclosure, natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and at least one polyol compound consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof, were selected in a ratio range of 1:1 to 6:4, respectively, to prepare a multifunctional novel excipient using twin-screw hot melt extrusion, wherein the Carr index was in the range of 28-13% and the water retention of the ratio was in the range of 6-10 times its own weight.

[0045] In one embodiment of the present disclosure, the co-processed multifunctional novel excipients prepared using twin screw extrusion were evaluated for parameters such as physical properties, FTIR testing, water absorption / retention, and toxicity. The evaluation details are as follows:

[0046] a) Physical properties: The physical properties of the multifunctional novel excipients prepared using a twin-screw extruder are shown in Table 2.

[0047] [Table 2]

[0048] b) FT-IR analysis of the samples: Infrared (IR) spectra of organic molecules yield valuable information about the various functional groups present in them. In this study, IR spectra of natural coconut husk, and / or coir pith powder derived from coconut husk, coir pith powder derived from the fruit of Cocos nucifera, and at least one polyol compound were recorded using a diffuse reflectance assembly. Prior to this, the samples were pulverized in dry KBr and a homogeneous solid solution containing 1–2% of the substance was used for recording the IR spectra. Figure 3 shows the IR spectrum of the treated functional excipient sample. The main peaks are at 3400, 2900, 1730, 1600 and 1510 cm. -1 2800-3000 and 3300-4000 cm -1 The peaks at 1510 and 1600 cm are due to aliphatic CH and OH stretching vibrations. -1 The value at 1730 cm is for aromatic skeletal vibration (of lignin). -1 The small absorption of is thought to be due to the ester group (minor component).

[0049] c) Water retention Water retention is defined by the volume of water bound to the fibre containing the usable excipients without the application of external forces (except gravity and atmospheric pressure). Accurately weighed dry samples (1 g) were taken into two graduated test tubes and approximately 30 ml of water was added and allowed to hydrate for 3 and 18 hours, respectively. The supernatant was extracted by passing through a vacuum in a sintered glass crucible (G4). The weight of the hydrated residue was recorded and dried at 105 °C for 2 hours to obtain the residual dry weight. Water retention (g / g) = (weight of hydrated residue - dry weight of hydrated residue) / dry weight of hydrated residue (Thibault, JF et al). The water retention was found to be in the range of 6-10 and 15-20 times the self-weight of the functional excipients, respectively.

[0050] d) Toxicity: Toxicity studies in rats showed no toxic effects up to 72 hours. Since this functional excipient has not been reported anywhere in the literature as an excipient, toxicity studies were prioritized to support the use of this novel functional excipient in pharmaceuticals, nutraceuticals and / or cosmetics.

[0051] e) Scanning Electron Microscope (SEM) To observe the surface characteristics such as porosity and particle size of the co-processed multifunctional novel excipient prepared using twin-screw hot melt extrusion, surface images were taken using SEM. As shown in Figure 4, a smooth surface and high porosity were observed in the SEM image at 10 kV and 300x magnification.

[0052] f) Particle size distribution The mean particle size analysis of the co-processed multifunctional novel excipients prepared using twin-screw hot melt extrusion technique was carried out using a Mastersizer 2000 MU (Malvern Instruments, UK). Sample preparation was performed following appropriate standard operating procedures (SOPs) (approximately 0.3-0.5 g of sample was dispersed in 900 ml of appropriate solvent (water and ethanol, assisted by sonication)). Particle size distribution was observed at d10-19.338 μm, d50-51.30 μm, d90-110.49 μm as shown in Figure 5.

[0053] From the above results, it can be concluded that the co-processed multifunctional novel excipient prepared using twin-screw extrusion exhibits excellent water absorption / retention due to high porosity and self-lubrication as evident from the porosity and Carr index.

[0054] In one embodiment of the present disclosure, the examples set forth below are intended to illustrate various aspects of the co-processed multifunctional novel excipients prepared using twin-screw extrusion and are not intended to be limiting solely to the scope of the claims.

[0055] [Example] Example 1: Desiccant / desiccator during wet granulation of metformin hydrochloride IR tablets The above co-processed multifunctional novel excipients are efficient drying agents. For example, they can be used in wet granulation process and do not require evaporation of large amount of water. The drug was mixed with lactose and croscarmellose sodium separately. An aqueous solution of polymeric binder was prepared and used as binder. A wet mass of drug-excipient mixture was prepared with binder solution. The wet mass was sieved using suitable sieve with mesh size #6-12 screen to obtain granules. The wet granules were dried at 40-50°C for 30 minutes and sieved through sieve with mesh size #14-20. The granules after drying and sieving were mixed with lubricant. Both drying and milling steps in wet granulation were not required for Batch I formulation. Carr index, angle of repose, and Hausner ratio of granules were found to be in the range of excellent to good flowability as per USP limits.

[0056] [Table 3]

[0057] Example 2: Thickener for topical application to external parts of the skin (human / animal) In one embodiment of the present disclosure, a functional excipient is provided for use as a thickener for the preparation of semi-solid dosage forms such as ointments, gels, creams, etc. It can be used as a pharmaceutical, nutraceutical, and / or cosmetic agent for topical application to the external parts of the skin (human / animal). The preparation of such a thickener includes ingredients consisting of: a. 0.5-3% by weight, preferably 0.8-1.5% by weight, of various coconut husks and / or coir piss powders; b. 97-99.5% by weight, preferably 98-99.2% by weight of water / any suitable fluid as a vehicle. Table 4 shows the results of the thickeners prepared.

[0058] [Table 4]

[0059] Example 3: Design and Development of a Transdermal Patch for the Relief of Rheumatoid Arthritis (RA) A transdermal patch containing ginseng oil (8.4±0.12ml / g of absorbent) on the absorbent was prepared using HPMC and PEG-400 by solvent casting method. The polymer was dissolved in 20ml of hydroalcoholic solution and placed on a magnetic stirrer at 60 rpm. The co-processed multifunctional novel excipient containing ginseng oil was transferred to the above mixture in the presence of PEG-400 (plasticizer) and DMSO (penetration enhancer). The area of ​​the patch was 36.29cm after making the mixture into a volume of 25ml. 2 The patches were cut into sizes (2 × 2 cm) each containing 1.2 ml of oil. 2 The prepared patches were stored in a desiccator for further evaluation. To finalize the concentrations of HPMC and PEG, six types of patches were prepared with different concentrations of HPMC and PEG (Table 5).

[0060] [Table 5]

[0061] Various parameters were evaluated for the prepared patches in triplicate, and the results were calculated as mean ± standard deviation. The thickness of the prepared formulation was checked in triplicate at different positions of the patch using a Digimatic Micrometer (Mitutoyo, ABSOLUTE). The results ranged from 0.32 ± 0.0447 mm to 0.34 ± 0.0537 mm. No effect of the concentration of HPMC and PEG on the thickness of the patch was observed. The prepared formulation was subjected to a weight variation test. Three patches were randomly selected from every batch and weighed. The average weight was found to be in the range of 0.193 ± 0.032578 to 0.220 ± 0.04875 gm / 2 square inches (2 × 2). It was found that the weight of the patch increased as the concentration of the polymer increased. The prepared patches were evaluated by a folding durability test in which the patch was folded continuously at the same position until it broke (NMT300 times). The folding durability of the patches was found to be in the range of 145 ± 0.20 to 158 ± 0.25. The change in the concentration of HPMC and PEG affected the folding durability. The tensile strength of the patches was measured by a "CT-3 Texture Analyzer" testing machine. The tensile strength was 2.425 ± 0.15 to 3.370 ± 0.16 (MPa / mm). The concentration of polymer and plasticizer showed a positive effect on the tensile strength. Next, the moisture loss rate of the prepared formulations was examined by placing the prepared patches in a desiccator in the presence of anhydrous calcium chloride. After 72 hours, the weight change of the film was checked. The moisture loss rate was calculated using Equation (1). The moisture content of all the developed formulations was found to be in the range of 2.252 ± 0.90 to 7.151 ± 1.44%, as shown in Table 6. The moisture content of the patches was found to be the optimum level to maintain stability and prevent complete drying and destruction. All the results are shown in Table 5.

[0062]

number

[0063] [Table 6]

[0064] Furthermore, prior to preclinical testing, oil release from the patch was confirmed using Franz diffusion cells. Alcoholic phosphate buffer (pH 7.4) was used as the diffusion medium. The prepared patch was placed on a cellophane membrane (previously soaked in buffer for 8 h) and carefully clamped between the donor and receptor compartments. The whole was placed on a magnetic stirrer and maintained at 32 ± 0.5 °C. Samples (1 ml each) were withdrawn after 1, 2, 3, 4, 6, 8, 10, and 12 h and analyzed by HPTLC. Densitometric scanning was performed on a Cagmag TLC scanner 3 in absorbance mode and operated at 374 nm with winCATS software. A sink condition was maintained by adding an equal volume of buffer to the receptor compartment. The in vitro oil release test results showed that the release of ginseng oil from the prepared patches increased at a certain time interval up to 8 h (6.18±0.12%, 19.56±1.52%, 32.14±1.87%, 45.31±2.04%, 76.28±2.11%, and 99.41±1.31%, respectively), after which the release decreased, i.e., the total release was obtained (Figure 6). Based on the obtained results, batch F6 was considered as the optimized batch and was subjected to preclinical testing.

[0065] To confirm the efficacy of the optimized ginseng oil-containing transdermal patch, an anti-inflammatory test (carrageenan-induced hind paw edema method) was performed using 18 male Wistar rats weighing 142-151 g. The animals were kept under standard laboratory conditions and diet according to guidelines. The animals were randomly divided into three groups: control group (I), oil-treated group (II), and patch-treated group (III). Edema was induced by injection of 0.1 ml of 1% λ-carrageenan-saline solution (22049 SIGMA λ-carrageenan vegetable mucopolysaccharide, Sigma-Aldrich). The thickness of the paw edema was measured for 4 hours using a standard Digital Vernier caliper. The formulation showed a better reduction in paw edema compared to the application of pure oil. The results are shown in Figure 7. After 6 hours, the animals were anesthetized and sacrificed by cervical dislocation. Blood samples were taken from the treatment sites and analyzed for IL-6 using an ELISA kit according to the manufacturer's instructions. The results showed that the levels of IL-6 were significantly elevated in animals from groups I and II compared to those from group III (Figure 8). Increased IL-6 is an important early marker of arthritis. The obtained results further support the usefulness of the proposed treatment in arthritis.

[0066] In one embodiment of the present disclosure, the prepared transdermal patch based on the co-processed multifunctional novel adsorbent containing ginseng oil showed compelling results compared to regular topical application of ginseng oil, i.e., the conventional method. This may be due to the increased contact time, the presence of permeation enhancers, and / or the pressure of the patch. Therefore, based on the available body of evidence, it can be concluded that the prepared patch has a good potential in the management of arthritis compared to the conventional approach.

[0067] Example 4. Development and evaluation of luliconazole powder using s-SMEDDS method In an embodiment of the present disclosure, a luliconazole powder is developed using a solid self-emulsifying drug delivery system (s-SMEDDS). Luliconazole has poor solubility, transdermal permeability and stability. Therefore, a surface adsorption technique for luliconazole was developed, which can improve the solubility, transdermal permeability and stability of luliconazole. The formulated liquid SMEDDS was further converted into a solid SMEDDS by surface adsorption using a co-processed multifunctional novel excipient. Furthermore, the solid SMEDDS had improved permeability and formulation stability. In vitro drug release and permeation tests showed that the prepared formulation had a drug release capacity of approximately 48 μg / cm 2 In the skin irritation test, neither preparation caused any edema or redness on the skin, and it was concluded that the prepared preparations were suitable for topical use. In the antifungal activity test, cultures of A. niger and C. albicans were performed, but neither fungal species grew.

[0068] The PXRD pattern of solid SMEDDS showed no peaks indicating polymorphic transition at the molecular level. The disappearance of the prominent peaks for pure luliconazole indicated that the crystal structure of luliconazole changed dramatically to amorphous form after preparation of solid SMEDDS (Figure 9).

[0069] The optimized SMEDDS powder showed optimal antifungal activity against Candida albicans, one of the major fungal pathogens of humans, and as seen in Figure 10, the optimized powder showed a larger zone than the commercial one, indicating stronger antifungal activity. The prepared formulation showed its action by inhibiting the formation of ergosterol in the cell walls of fungal species.

[0070] There was no evidence of erythema or signs of edema observed at the application site after 24, 36, 48 and 72 hours (Figure 11). This indicated the non-irritating nature of the prepared formulation when applied to the skin. Hence, all excipients used in the formulation were found to be non-irritating and safe for topical application.

[0071] Those skilled in the art will recognize that the present disclosure is subject to variations and modifications other than those specifically described. The present disclosure is to be understood to include all such variations and modifications. The present disclosure also includes all such steps, features, compositions, and compounds referred to or shown herein, individually or collectively, and any and all combinations of any or more of such steps or features. [Brief description of the drawings]

[0072] [Figure 1] Some high-performance excipients available on the market are listed below. [Diagram 2] Experimental design for preparing co-processed multifunctional novel excipients. [Diagram 3] 1 shows an FTIR analysis of the functional excipients described in the present invention. [Figure 4] SEM of co-processed multifunctional novel excipients. [Diagram 5] Particle size distribution of co-processed multifunctional novel excipients. [Figure 6] In vitro drug release study with HPTLC batch densitogram of formulation batch F6. [Figure 7] Paw edema measurements: a) 0 min, b) 60 min, c) 120 min, d) 180 min, e) 240 min (Note: data are expressed as mean ± SEM and analyzed by one-way ANOVA followed by Bonferroni's multiple comparison post-test). [Figure 8] Transdermal patch IL-6 measurements (Note: data are expressed as mean ± SEM and analyzed by one-way ANOVA followed by Bonferroni's multiple comparison post-test). [Figure 9] PXRD patterns of formulations and raw materials. [Figure 10] Antifungal activity by petri plate assay. [Figure 11] Skin irritation test results: A) initial; B) after 24 hours; C) after 48 hours; D) after 72 hours.

Claims

1. (a) natural coconut husk and / or coir piss powder derived from the husk of the coconut, the fruit of Cocos nucifera; and (b) at least one polyol compound selected from the group consisting of glycerol, sorbitol, polyethylene glycol (PEG), propylene glycol (PG), and combinations thereof; wherein the weight ratio of (a) to (b) ranges from 1:1 to 6:4, A method for producing a co-processed multifunctional excipient, comprising the step of subjecting a mixture containing (a) and (b) in a weight ratio of (a) to (b) in the range of 1:1 to 6:4 to a twin-screw hot melt extrusion at an ambient temperature of 60 to 110°C and a screw rotation speed in the range of 25 to 60 rpm.

2. 2. The method for producing natural coconut husk and / or coir apis powder co-processed multifunctional excipients from the husk of coconut, the fruit of Cocos nucifera, according to claim 1, wherein the water retention capacity of the co-processed multifunctional excipients is in the range of 6 to 10 times its own weight.

3. 3. A method for producing a co-processed multifunctional excipient of natural coconut husk and / or coir pith powder from the husk of coconut, the fruit of Cocos nucifera, according to claim 1 or 2, wherein the coconut husk and / or coir pith powder are used as absorbents.

4. 3. A method for producing a co-processed multifunctional excipient of natural coconut husk and / or coir apis powder from the husk of coconut, the fruit of Cocos nucifera, according to claim 1 or 2, wherein at least one polyol and / or a combination of more polyols increases the bulk density of the particles.

5. A method for producing a co-processed multifunctional excipient of natural coconut husk and / or coir apis powder derived from the husk of coconut, the fruit of Cocos nucifera, as described in claim 1 or 2, wherein the co-processed multifunctional excipient is used as a multifunctional ingredient such as an absorbent, scavenger, flow improver, thickener, and / or viscosity enhancer.

Citation Information

Patent Citations

  • Sludge activated carbon loaded with copper-based catalyst as well as preparation method and application of sludge activated carbon

    CN115770571A

  • Manufacture of high strength carbonaceous structure by extrusion molding method

    JP1981050106A

  • Formulations containing particles

    JP2017524720A

  • Pharmaceutical excipient having improved compressibility

    US20030099702A1

  • Compressed Coconut Coir Pith Granules and Methods for the Production and use Thereof

    US20090113791A1